1993
DOI: 10.1111/j.1748-8583.1993.tb00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Commitment Be Managed? A Longitudinal Analysis of Employee Commitment and Human Resource Policies

Abstract: Tim Morris, Helen Lydka and Mark Fenton O'Creevy present data on a group of graduates during the first five years of employment. Dividing the sample into those who have remained with their original employer and those who have changed, they examine attitudinal commitment and tenure intentions against a set of human resource policies measured at three points in time. They find that those policies significantly associated with high commitment change over time; that attitudinal and behavioural commitment are conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
70
0
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 53 publications
15
70
0
6
Order By: Relevance
“…This finding agrees with previous findings that link commitment to organisational commitment (Purang, 2008) autonomy (Wallace et al, 1996), supervisor support (Benson, 1996) cohesiveness (Buchanan, 1974), formal workplace training (Bartlett, 2001;Kontoghiorghes and Bryant, 2001;McMurray and Dorai, 2001;Caldwell et al 1990, Morris et al, 1993, open culture, a learning climate and organizational support for training and personal development (Visser and van der Sluis, 2006;Gründemann et al, 2005).…”
Section: Insert Figure 1 About Heresupporting
confidence: 83%
See 1 more Smart Citation
“…This finding agrees with previous findings that link commitment to organisational commitment (Purang, 2008) autonomy (Wallace et al, 1996), supervisor support (Benson, 1996) cohesiveness (Buchanan, 1974), formal workplace training (Bartlett, 2001;Kontoghiorghes and Bryant, 2001;McMurray and Dorai, 2001;Caldwell et al 1990, Morris et al, 1993, open culture, a learning climate and organizational support for training and personal development (Visser and van der Sluis, 2006;Gründemann et al, 2005).…”
Section: Insert Figure 1 About Heresupporting
confidence: 83%
“…In a study by Lowry et al (2002) there is an indications that the availability and adequacy of training affected job satisfaction and commitment levels of employees. Researches (Caldwell et al 1990, Morris et al, 1993 have also shown the effect of availability of training on employee commitment. Studies (Brinkerhoff and Montensio, 1995;Huczynski and Lewis, 1980;Michalak, 1981;Tracey et al, 1995) showed the influence of the immediate supervisor in encouraging or discouraging usage of training.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Iverson (1996) appealed that job security has momentous effect on the organizational pledge. Morris et al (1993) resulted the same. It was found that job performance and organizational assurance are destructively connected with job insecurity (Rosenblatt and Ruvio, 1996).…”
Section: Job Safety and Securitysupporting
confidence: 59%
“…Moreover, the notion and concept of the co relationship existence between the training and development program availability and organizational commitment is highlighted by work of (Morris et al, 1993;Guest et.al, 2003;Wall & Wood (2005).…”
Section: Job Satisfaction Organisational Commitment and Training Promentioning
confidence: 99%